Unexpected Second Primary Malignancies Detected by F-18 FDG PET/CT During Follow-up for Primary Malignancy: Two Case Reports - Bang, Ji-In (Nucl Med Mol Imaging, 2014)
As the survival rate of cancer patients has increased over the last few decades, the risk of cancer survivors developing second primary malignancies has gained attention. We report two rare cases of second primary hematologic malignancy detected by (18)F-fluorodeoxyglucose (F-18 FDG) positron emission tomography/computed tomography (PET/CT) during follow-up for primary solid malignancies. Acute lymphoblastic leukemia developed in a breast cancer patient and non-Hodgkin lymphoma in an anal cancer patient. F-18 FDG PET/CT findings led to the diagnosis of unexpected second primary hematologic malignancy in cancer survivors in these two cases.